2021
DOI: 10.3389/fsoc.2021.675618
|View full text |Cite
|
Sign up to set email alerts
|

Occupation-Based Life Expectancy: Actuarial Fairness in Determining Statutory Retirement Age

Abstract: This study examines occupation-based differences in life expectancy and the extent to which health accounts for these differences. Twentyseven-year survival follow-up data were used from the Dutch population-based Longitudinal Aging Study Amsterdam (n = 2,531), initial ages 55–85 years. Occupation was based on longest-held job. Results show that the non-skilled general, technical and transport domains had an up to 3.5-year shorter life expectancy than the academic professions, accounting for the compositional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Although the population is getting older and a larger proportion of the working population continues to work longer, there are significant social differences. Previous research shows, among other things, that some occupational groups have a shorter life expectancy (Deeg et al 2021) and also a lower retirement age than other occupational groups. This may be because they are less able to continue working due to strenuous work tasks, reduced work ability or limited employability because of lower qualifications.…”
Section: Theoretical Framework For Analysis Of Social Inequality In T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the population is getting older and a larger proportion of the working population continues to work longer, there are significant social differences. Previous research shows, among other things, that some occupational groups have a shorter life expectancy (Deeg et al 2021) and also a lower retirement age than other occupational groups. This may be because they are less able to continue working due to strenuous work tasks, reduced work ability or limited employability because of lower qualifications.…”
Section: Theoretical Framework For Analysis Of Social Inequality In T...mentioning
confidence: 99%
“…It therefore reduces the risk of deteriorating health with continued strenuous work and can be considered a preventive measure. Previous research indicates that certain occupational groups have a lower life expectancy (Deeg et al 2021). Allowing early retirement for these groups could equalize the time as a pensioner compared to the rest of the population.…”
Section: Options For Early Retirement For People In Certain Professio...mentioning
confidence: 99%
“…The sole consequence of hazardous work that is not addressed by any branch of the social insurance system is the reduction of life expectancy. There are some studies linking worker’s occupation to mortality (Johnson, Sorlie and Backlund, 1999; Katikireddi et al, 2017; Lee et al, 2016) or life expectancy (Moore and Hayward, 1990; de Wind et al, 2020; Deeg, Tavernier and de Breij, 2021). The estimates provided by these range from a maximum difference between favourable and unfavourable working conditions of around 2.5 years (de Wind et al, 2020) to 4.5 years at age 55 (Moore and Hayward, 1990), and around 3.3 years at age 65 (Deeg, Tavernier and de Breij, 2021).…”
Section: Potential Functions Of Special Pension Schemesmentioning
confidence: 99%
“…Blumel and colleagues' model showed that being in an unskilled job was an independent risk factor for reduced longevity. A large part of the reduced life expectancy associated with being in an unskilled job is likely due to poorer health of people working in unskilled jobs as evidenced by their sick days, use of medication, hospital admissions, and outpatient visits 20 . Given this, it is unlikely that recommending a woman changes her job at midlife (even if it was feasible to do so) would influence her future longevity; however, there may be occupational exposures to hazardous materials that are modifiable.…”
mentioning
confidence: 99%
“…A large part of the reduced life expectancy associated with being in an unskilled job is likely due to poorer health of people working in unskilled jobs as evidenced by their sick days, use of medication, hospital admissions, and outpatient visits. 20 Given this, it is unlikely that recommending a woman changes her job at midlife (even if it was feasible to do so) would influence her future longevity; however, there may be occupational exposures to hazardous materials that are modifiable. It would be possible for a clinician to focus on the health literacy of a woman in an unskilled job to assist her to modify other risk factors she may have for reduced longevity.…”
mentioning
confidence: 99%